LOS TIEMPOS ESTÁN CAMBIANDO: EL OPENING DE WATCHMEN (2009) COMO PARADIGMA DE LA CONSTRUCCIÓN DEL SUPERHÉROE POSCLÁSICO - MONTAÑANA-VELILLA, JORDI,Dra. MARTÍN-NÚÑEZ, MARTA (Fonseca, Journal of Communication, 2023)
American superheroes have transited and redefined themselves in a transversal way as icons of reference of the cultural industries throughout the multiple creative stages that have taken place in the art of comics. The abandonment of strongly stereotyped classical heroic figures has favored the construction of a post-classical heroic subject that moves towards more complex and traumatic paths. The migration of superhero stories from comics to screens has made possible their projection in a new media ecosystem and through significant narrative strategies developed in the openings of superhero serials and movies, their evolution and mutation is recognized.